2010
DOI: 10.3802/jgo.2010.21.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of laparoscopic versus conventional open surgical staging procedure for endometrial cancer

Abstract: Objective: The aim of this study was to compare the surgical outcomes of laparoscopic surgery and conventional laparotomy for endometrial cancer. Methods: A total of 104 consecutive patients were non-randomly assigned to either laparoscopic surgery or laparotomy. All patients underwent comprehensive surgical staging procedures including total hysterectomy, bilateral salpingo-oophorectomy, and pelvic/para-aortic lymphadenectomy. The safety, morbidity, and survival rates of the two groups were compared, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 35 publications
1
21
1
2
Order By: Relevance
“…Alternatively, only 2 (11.1%) of the genitourinary complications were associated with minimally invasive surgery. This is consistent with previous studies that reported higher complication rates following an open procedure compared with laparoscopic surgery [18,19,21,22]. …”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, only 2 (11.1%) of the genitourinary complications were associated with minimally invasive surgery. This is consistent with previous studies that reported higher complication rates following an open procedure compared with laparoscopic surgery [18,19,21,22]. …”
Section: Discussionsupporting
confidence: 83%
“…Kong et al also compared the surgical outcomes of laparoscopic surgery and open surgery in patients with endometrial cancer [34]. Patients undergoing laparoscopy had on average 4 more lymph nodes removed and 11.7% of these patients were diagnosed with a lymphocyst while 10% of patients undergoing laparotomy were diagnosed with a lymphocyst.…”
Section: Long-term Risks Of Lymph Node Dissectionmentioning
confidence: 99%
“…Endometrial cancer is the most common gynecological malignancy and the fourth most frequent site of malignant neoplasm in females [3]. Endometrial cancer comprises only 1.9% of all types of cancer in increasing trend along with the average lifespan [4].…”
Section: Introductionmentioning
confidence: 99%